(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
Micro enterprises formed the majority of business establishments in Malaysia and contributed significantly to the nation’s economy. Most knowledge-sharing studies focus on large, medium, and small enterprises as they are seen as more important. Very little researches dedicate to microenterprises, although it is crucial to the economy. The partial-least square analysis of one hundred and six micro-enterprises found that tacit knowledge sharing has a more substantial impact on organizational performance through entrepreneurial orientation. Tacit knowledge sharing is widely used in microenterprises and has a significant influence on organizational performance in Malaysia. Limitations and implications for future studies are discussed.